Hyperprolactinemia associated with macroprolactinoma in a 17-year-old: A case report - Adam Czyzyk; Rafal Kurzawa (Elsevier, 2019)
Hyperprolactinemia is a relatively common endocrine disorder. In women of reproductive age it may present as the amenorrhea-galactorrhea syndrome, but in milder forms also as menstrual abnormalities or infertility. Here we describe a 17-year-old girl previously treated with a combined oral contraceptive due to secondary amenorrhea. Hormonal tests showed hypogonadotropic hypogonadism with severe hyperprolactinemia (PRL concentration 1639 ng/ml). Further tests confirmed the presence of a pituitary macroadenoma. Cabergoline treatment was effective in the restoration of a spontaneous menstrual cycle and PRL normalization. In conclusion, clinicians should be aware of the diagnostic and therapeutic problems in the management of hyperprolactinemia. Keywords: PRL, Hyperprolactinemia, Prolactinoma, Secondary amenorrhea